Evaluation Forum recommends continuation of CTA's SDI service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In 1988, CTA launched its Selective Dissemination of Information (SDI) project, a literature service for senior ACP research scientists to allow them to keep abreast of the latest scientific and technical information relevant to their field of...